MAKING CONTINENTAL CRUST THROUGH SLAB MELTING: CONSTRAINTS FROM NIOBIUM-TANTALUM FRACTIONATION IN UHP METAMORPHIC RUTILE - Xiao Y.; Hoefs J.; Simon K.; Li S.; Sun W.; Hofmann A.W.; Zhang Z. (My University, 2006)
The formation of the continental crust (CC) is one of the most important processes in the evolution of the silicate Earth. Exactly how the CC formed is the subject of ongoing debate that focuses on its subchondritic Nb/Ta ratio. Nb and Ta are "geochemical identical twins," so they usually do not fractionate from each other. Here, we show that rutile grains from hydrous rutile-bearing eclogitic layers recovered from drillcores in the Dabie-Sulu ultrahigh pressure terrain have highly variable Nb/Ta values (ranging from 5.4 to 29.1, with an average of 9.8 ± 0.6), indicating major fractionation of Nb and Ta most likely occurred during blueschist to amphibole-eclogite transformation in the absence of rutile. It is suggested that the released fluids with subchondritic Nb/Ta were transported to, and retained by, hydrous rutile-bearing eclogite in colder regions, resulting in suprachondritic Nb/Ta ratios for drier eclogite in hotter regions. Further dehydration of hydrous rutile-bearing eclogites cannot transfer the fractionated Nb/Ta values to the CC due to the low solubility of Nb and Ta in fluids in the presence of rutile, while dehydration-melting results in a major component of the CC, the tonalite-trondhjemite-granodiorite (TTG) component, which is responsible for the low Nb/Ta of the CC. Consequently, residual eclogites have variable but overall suprachondritic Nb/Ta. © 2006 Elsevier Inc. All rights reserved.